Análisis Del Grado De Motivación De Los Profesores En Las Escuelas De Enseñanza Primaria De La Periferia De La Zona "B" En Benguela (Angola) En El Desarrollo De Sus Actividades Docentes - Terezinha Ernesto; Juan Manuel Trujillo Torres; Esther Garzón Artacho (European Scientific Journal, ESJ, 2017)
The article aims to analyze the degree of professional motivation of the teachers of primary schools in the periphery of zone B in the development of their teaching activities, in a population of 271 subjects and a final sample of 200 teachers and 4 directors. To carry out this research, a questionnaire was applied to teachers that follow a Likert scale, with 71 variables related to professional motivation. Interviews were also conducted with members of the selected schools. Different statistical analyzes were carried out for the processing of the collected information, such as the application of the test of the two halves of Guttmann and the coefficient of Spearman Brown, with a reliability of the results showing the internal consistency of the instruments used in this study (0.993). The results indicate that teachers outside schools have a professional motivation level lower than school teachers in urban areas, given the numerous labor difficulties they face daily in schools. From the perspective of teachers, their level of job satisfaction can improve when they see that the basic problems that have to do with their professional success are solved, including among these solutions the decrease in the number of students in the classes.